2019
DOI: 10.1002/lary.28315
|View full text |Cite
|
Sign up to set email alerts
|

Margins in Sinonasal Squamous Cell Carcinoma: Predictors, Outcomes, and the Endoscopic Approach

Abstract: Objectives: To identify factors associated with positive margins following surgical management of sinonasal squamous cell carcinoma (SNSCC), especially with regard to endoscopic treatment.Methods: In a retrospective analysis of adult patients with clinically staged tumor (T)1 to T4a SNSCC within the National Cancer Database (NCDB) from 2004 to 2014, factors were associated with positive margins using multivariable binary logistic regression. Cases from 2010 to 2014 had surgical approach (open vs. endoscopic) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
2
42
0
2
Order By: Relevance
“…We found a significantly high rate of positive margins (>40%) and they were broadly associated with increased mortality, similar to other HN malignancies 51,52 . However, as discussed, this varied by histology.…”
Section: Discussionsupporting
confidence: 83%
“…We found a significantly high rate of positive margins (>40%) and they were broadly associated with increased mortality, similar to other HN malignancies 51,52 . However, as discussed, this varied by histology.…”
Section: Discussionsupporting
confidence: 83%
“…In a study by Torabi et al, looking at SNSCC margin status, there was a statistically significant difference between high- and low-volume facilities in achieving negative margins. 32 However, they defined high-volume facilities as having ≥2 cases per year instead of a tertile grouping and excluded nonsurgical cases when tabulating facility case volume. Studies in laryngeal surgery and transoral robotic surgery have demonstrated improved negative margin rates at high-volume facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with prior studies where SCC patients with positive margins had a decreased OS and required additional use of adjuvant therapies. 23 Some advocate treating advanced-stage PDSCC with induction chemotherapy using taxane and platinumbased agents or taxanes and 5-fluorouracil followed by definitive CRT or neoadjuvant chemotherapy followed by surgery and adjuvant CRT. 24,25 In our study, we did not find evidence of a survival benefit with the use of induction, neoadjuvant, or adjuvant chemotherapy within the treatment regimen.…”
Section: Discussionmentioning
confidence: 99%